An uneventful pregnancy and delivery, in a case with chronic myeloid leukemia on imatinib - Jovita Martin; Anita Ramesh; Lalitha Devadasan; Palaniappan; Jude J Martin (Indian Journal of Medical and Paediatric Oncology)
The concomitant occurrence of pregnancy and chronic myelogenous leukemia is uncommon. We describe the successful management of a 24-year-old woman in the first trimester of her pregnancy with chronic myelogenous leukemia (CML) in the chronic phase, who was on treatment with imatinib, which was stopped by 10 th week of pregnancy. Until, she completed full term of pregnancy she was on hydroxyurea. The use of imatinib did not have adverse effects on the fetus. The patient had a normal vaginal delivery and gave birth to a healthy 2500 g girl at 37 weeks of gestation. We conclude that imatinib in the first trimester of pregnant lady with CML, though has particular concern regarding the potential teratogenic and other adverse effects, has shown evidences of safe conception, pregnancy and delivery in ladies with CML.